2012
DOI: 10.1002/aic.13870
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and kinetics analysis of carbon dioxide capture using immobilized amine on a mesoporous silica

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Thermogravimetric analysis is used to study the adsorption kinetics, equilibrium, and thermodynamics of CO 2 on immobilized polyethylenimine sorbent impregnated on a mesoporous silica over the range of 300-390 K and 5-100% CO 2 concentration. Adsorption isotherm models were fitted to the experimental data indicating that a change in adsorption mechanism occurred near 70 C. Below this temperature, the adsorption data followed the heterogeneous isotherms, while da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
121
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 39 publications
11
121
0
1
Order By: Relevance
“…In this regard, catalytic CO 2 methanation for the synthesis of fuels and valuable products has attracted considerable interest. 1,2 Numerous supported catalysts based on group VIII (noble metals) based supported catalysts have been tested for CO 2 methanation. [3][4][5][6][7] Notably, Ni catalysts supported on oxide supports were most widely applied attributed to their higher activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, catalytic CO 2 methanation for the synthesis of fuels and valuable products has attracted considerable interest. 1,2 Numerous supported catalysts based on group VIII (noble metals) based supported catalysts have been tested for CO 2 methanation. [3][4][5][6][7] Notably, Ni catalysts supported on oxide supports were most widely applied attributed to their higher activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…More information is available on the adsorption process. Kinetic analysis for fluid bed adsorption in these sorbents was consistent with the TGA data [24,29]; however, the proposed nucleation and growth rate expressions are too numerically unstable to incorporate into computationally intensive CFD models.…”
Section: Introductionmentioning
confidence: 53%
“…Monazam et al [29] found that a mesoporous PEI based sorbent exhibits 2-dimensional nucleation growth diffusion controlled rates within this composite structure. The adsorption rate is controlled by the transport of CO 2 into the deeper PEI layers in the mesopores.…”
Section: 2mentioning
confidence: 99%
“…35 Meanwhile, 1/n < 1 also corresponds to a normal L-type Langmuir isotherm. 32,36 Moreover, the presence of solvent water also can decrease the heterogeneity of SSDB surface. 37 Based on these views, the Langmuir isotherm may be a better model which indicates the adsorbent surface is described by homogeneous adsorption sites.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…32,33 The Langmuir model assumes monolayer surface coverage on equivalent sites. The Freundlich model, on the other hand, assumes a heterogeneous adsorption surface with sites that have different adsorption energies.…”
Section: Adsorption Isothermsmentioning
confidence: 99%